Función sexual en mujeres postmenopáusicas con y sin terapia de reemplazo hormonal (TRH) - Delfor Seminario, Ángel (2015)
Función sexual en mujeres postmenopáusicas con y sin terapia de reemplazo hormonal (TRH).